Memoirs of Huseyn Shaheed Suhrawardy with a brief account of his life and work - Talukdar, Mohammad H. R. (Mohammad Habibur Rahman) (Dhaka : University Press, 1987)
Memoirs of a former chief minister of Bengal and prime minister of Pakistan, chiefly on politics in Pakistan; includes his biography by the editor.
Includes bibliographical references (pages [229]-245) and index.
Donated By Akbar Ali Khan
Keywords: Suhrawardy, Huseyn Shaheed, -- 1892-1963.; Prime ministers -- Pakistan -- Biography; Politicians -- India -- Bengal -- Biography; Pakistan -- Politics and government; Bengal (India) -- Biography